Penggunaan Pendekatan Keterampilan Proses Padapembelajaran Tematik Terpadu Untuk Meningkatkan Aktivitas Belajar Siswa - Anton Saputra; Firman Firman; Neviyarni Neviyarni (Universitas Negeri Padang, 2019)
This study aims to improve the students’ activities and learning outcomes in grade 3 of Public Elementary School 24 in Luak Bayau Sulit Air Kecamatan X Koto Diatas Kabupaten Solok. This research is a Classroom Action Research (PTK) that is an improvement in the learning process. In doing so, the study consisted of two cycles. Each cycle was held two meetings consisting of planning, action, observation, and reflection of each meeting. Results of the data analysis show that the using of the skill process approach can improve the student’s activities and thematic learning outcomes in the student’s crafts themed in grade 3 SD Negeri 06 Sulit Air Rawang. So that the learning activities of students in the first cycle with student’s average score of 66.7 (standard qualification), increased in the second cycle is on student’s average with 84.3 (good qualifying). On the other side, the learning outcomes of students in the first cycle with an average of 75.6 (good qualifying), also increased in the second cycle is the average score of 84.2 (better qualifying).